PD PID and fuzzy logic control of three link planar arm - Eroglu, E; Cansever, G; Kucukdemiral, IB; Dalci, B (POZNAN UNIV TECHNOLOGY, 2004)
In this study we consider the control of a three link planar robot manipulator. Specifically we use PD, PID and Fuzzy type controllers. We then illustrate how PD, PID controllers can be design. We also illustrate how to design a fuzzy logic controller for the robot manipulator. We follow computed torque method strategy to develop our controllers. We try to find advantages of each control law by simulations. Simulation results are included to illustrate the performance of the controllers.
Keywords: Robotics